2002
DOI: 10.1074/jbc.m207509200
|View full text |Cite
|
Sign up to set email alerts
|

FOXO Proteins Regulate Tumor Necrosis Factor-related Apoptosis Inducing Ligand Expression

Abstract: Mutations in PTEN occur in 60 -80% of prostate cancers and lead to a constitutive activation of the phosphatidylinositol 3-kinase pathway and a resultant loss of activity of the FOXO family of forkhead transcription factors FKHRL1 and FKHR. To provide insight into the role of PTEN mutations in prostate cancer, we used microarrays to identify genes regulated by FKHRL1 and FKHR in LAPC4 prostate carcinoma cells. These studies revealed that adenoviral overexpression of FKHRL1 and FKHR in the LAPC4 prostate cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
303
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(317 citation statements)
references
References 43 publications
10
303
0
4
Order By: Relevance
“…Activation of these forkhead transcription proteins induces apoptosis through regulation of proapoptotic proteins including Fas ligand, TRAIL, and Bim in cancer cell lines [19,22,23]. Therefore, it seems possible that the higher the FKHR levels, the higher the tumor-suppressing effect FKHR would produce.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of these forkhead transcription proteins induces apoptosis through regulation of proapoptotic proteins including Fas ligand, TRAIL, and Bim in cancer cell lines [19,22,23]. Therefore, it seems possible that the higher the FKHR levels, the higher the tumor-suppressing effect FKHR would produce.…”
Section: Discussionmentioning
confidence: 99%
“…Skp2 overexpression reduced FOXO3-mediated transcription, whereas Skp2 knockdown increased FOXO3 transactivation (Figures 3d and e). Furthermore, we found that Skp2 knockdown resulted in an increased expression of a FOXO3 target gene, tumor necrosis factor-related apoptosis inducing ligand (TRAIL) (Modur et al, 2002;Fu et al, 2009) (Figure 3f). Repression of Skp2 expression also enhanced cell death (Figure 3g).…”
Section: E3 Ubiquitin Ligase Subunit Skp2 Downregulates Foxo3 Proteinmentioning
confidence: 99%
“…Consistent with decreased CAT and SOD gene expression, the level of reactive oxygen species was significantly increased in PC3 cells upon NAMPT inhibition (Figure 8b). FOXO3a is a direct transcriptional activator of CAT and SOD promoters (Kops et al, 2002;Nemoto and Finkel, 2002), and is highly expressed in prostate cancer cell lines (Modur et al, 2002). Whereas nuclear localization of FOXO3a is seen in normal prostate cells, increasing cytoplasmic accumulation of FOXO3a occurs in more advanced prostate cancer (Shukla et al, 2009).…”
Section: Nampt Is Overexpressed In Human Prostate Cancermentioning
confidence: 99%